2008
DOI: 10.1038/eye.2008.203
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcome following cataract extraction in patients aged 90 years and older

Abstract: Purpose To analyse surgical outcomes following cataract surgery in patients aged 90 years and older. Methods A retrospective case series of 78 patients aged 90 years or more (82 eyes) undergoing cataract extraction between 2000 and 2006 was performed. Age, sex, ocular comorbidities, surgical reports, preoperative and postoperative visual acuity (VA), and postoperative complications were recorded. A comparison of visual outcome between different ocular comorbidity groups was performed. Results Average age was 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
10
0
4
Order By: Relevance
“…The result was comparable with the results of several studies investigating the visual outcome of individuals aged 90 and older in recent years (Appendix S1). Three studies showed that approximately 70% of very elderly adults achieved improvement in visual acuity . One study demonstrated that visual acuity improved in 94% of individuals aged 90 and older .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result was comparable with the results of several studies investigating the visual outcome of individuals aged 90 and older in recent years (Appendix S1). Three studies showed that approximately 70% of very elderly adults achieved improvement in visual acuity . One study demonstrated that visual acuity improved in 94% of individuals aged 90 and older .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcomes of cataract surgeries in individuals younger than 90 have been reported in the literature, but data regarding clinical outcomes in very elderly adults are limited (Appendix S1). Three previous studies reported that approximately 70% of very elderly adults could achieve improvement in visual acuity after cataract surgery . Small sample size or short duration of follow‐up constrained these studies.…”
mentioning
confidence: 99%
“…U literature nailazimo das u te vrednosti u jednoj studiji 22% a u drugoj 63% [7,8]. Upoređujući rezultat rada sa podacima iz literature zaključuje se da postoji visok stepen poklapanja.…”
Section: Diskusijaunclassified
“…U jednoj studiji zastupljenost senilne degeneracije makule je 47,4% a primarnog galukoma otvorenog ugla 24,5%, a u drugoj zastupljenost senilne degeneracije makule iznosi 15,5%, glaucoma 35%, neproliferativne dijabetičke retinopatije 6% i miopije 24%. [8,9] Pacijenti koji su operisali kataraktu udruženu sa drugim oftalmološkim oboljenjem (senilna degeneracija makule, miopija, glaukom, neproliferativna dijabetička retinopatija i sl.) imali su značajno poboljšanje prosečne vidne oštrine u odnosu na prosečne preoperativne vrednosti.…”
Section: Diskusijaunclassified
See 1 more Smart Citation